2022
DOI: 10.1017/s0031182022000956
|View full text |Cite
|
Sign up to set email alerts
|

Cell repertoire and proliferation of germinative cells of the model cestode Mesocestoides corti

Abstract: The phylum Platyhelminthes shares a unique population of undifferentiated cells responsible for the proliferation capacity needed for cell renewal, growth, tissue repair and regeneration. These cells have been extensively studied in free-living flatworms, whereas in cestodes the presence of a set of undifferentiated cells, known as germinative cells, has been demonstrated in classical morphology studies, but poorly characterized with molecular biology approaches. Furthermore, several genes have been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…In cestodes, different studies have identified a population of undifferentiated stem cells similar to the neoblast; known as germinative cells, they are involved in the parasite’s development and the transitions between its different life stages [ 29 ]. Moreover, they are the only cells that are mitotically active, self-renewing, and capable of differentiating into any type of somatic cell [ 30 , 31 ]. The biological functions of germinative cells are not well-understood, and their study is complicated due to the complex life-cycle of cestodes, which includes at least two hosts [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cestodes, different studies have identified a population of undifferentiated stem cells similar to the neoblast; known as germinative cells, they are involved in the parasite’s development and the transitions between its different life stages [ 29 ]. Moreover, they are the only cells that are mitotically active, self-renewing, and capable of differentiating into any type of somatic cell [ 30 , 31 ]. The biological functions of germinative cells are not well-understood, and their study is complicated due to the complex life-cycle of cestodes, which includes at least two hosts [ 32 ].…”
Section: Introductionmentioning
confidence: 99%